Analisis Keamanan Aplikasi Android Non Playstore Dengan Metode Digital Forensik Pendekatan Statis Dan Dinamis - Indra Gunawan (SIMETRIS, 2021)
The crime of cyberspace every year has increased, one of which is a data leak. The non-playstore Android application is not guaranteed its security because the application system only has access to special directories, and this is what complicates the installation process of non-playstore application users. In this study the author conducted a security analysis with 5 non-playstore applications with a static and dynamic approach, after experimenting using Wireshark and Network Miner software with the process of the process of the method of the method of the National Institute of Justice (NIJ) which was divided into five stages, namely identification, collection, collection, Collection Examination, Analysis, and Reporting have received evidence that the non-playstore application is suspected not guarantee user data security. In this monitored application which will later obtain digital proof of safe or whether or not Android applications from the threat level of crime by using a static method to dismantle the application and dynamic programs used to see the data security exposed whether there is a virus in the application and other data leaks. From this analysis it can be obtained by experimental results using Sofwere Wireshark and Network Miner to be analyzed. This study aims to analyze the vulnerability level of applications sourced from non-playstore with a threat level. The results obtained from the 5 applications are monitored, it is known that the MICHAT Lite and BIGO LIVE application has an extreme risk with 45% points, on the Rolling Scroll application, Flying Sketchboard is known to high risk high risk with 25% point, while the Car Engine crash application has a security level Moderate risk with a risk that is 20%. The conclusion of this study is that applications installed from third parties have a higher level of threat when compared to the official application on the Playstore